Seasonal variation of potential denitrification rate and enhanced denitrification performance via water-lifting aeration technology in a stratified reservoir—A case study of Zhoucun reservoir. (November 2018) - Zhou, Shilei; Xia, Chao; Huang, Tinglin; Zhang, Chunhua; Fang, Kaikai
Abstract: Zhoucun reservoir is one of the major water resources in Zao Zhuang city, northern China. The seasonal distribution of surface sediment denitrification rate and enhanced performance of denitrification via water-lifting aeration technology were explored using the acetylene-inhibition technique. Surface sediment denitrification rates ranged from 2.57 ± 1.32 to 923.90 ± 86.81 nmol N2 /(g dw·h), with the highest rates in November (ANOVA, p < 0.05) and significantly low rates in June, July, and August (ANOVA, p < 0.05), mainly because of the seasonal differences in nitrate concentration, water temperature, and sediment total nitrogen (STN). Meanwhile, the N2 /(N2 +N2 O) ratio (83.44–91.70% for the highest sediment denitrification period) indicated that N2 accounted for a majority of denitrification. Correlation analysis between various environmental factors and denitrification was conducted, and nitrate concentration, STN, low molecular weight organic carbon, the number of aerobic denitrifying bacteria, and the environmental parameters of oxidation-reduction potential (ORP), pH, electrical conductivity (EC), and chlorophyll a (Chl-a) presented significant relationships during the entire study period. On the basis of the multiple regression model, nitrate and low molecular weight organic carbon concentration were the most influential factors on denitrification variability. Moreover, the denitrification rates of the surface sediment clearly increased, from 5.28 to 13.22 nmol N2 /(g dw·h) to 1117.02–3129.47 nmol N2 /(g dw·h), which were higher than those in the non-operating year. This suggests that the denitrification in the sediment system could be enhanced in situ by water-lifting and aeration technology in the reservoir ecosystem. Highlights: Surface sediment denitrification rates exbibited significant seasonal difference (P<0.05). The nitrate and sediment total nitrogen were key limiting factor. The denitrification could be enhanced in situ by water-lifting aeration technology.